Development and test of an automatic height-adjusting cotton topper - Zhaoyang, Chen; Lei, Shi (International Journal of Agricultural and Biological Engineering, 2017)
A fine-tuned height-adjustable cotton topper was developed and evaluated in this study. Cotton is topped at the late flowering stage because spindling reduces cotton production and complicates harvest. The main disadvantage of traditional cotton toppers is that their topping height cannot be adjusted according to the heights of individual cotton plants, resulting in a high percentage of missed tops and overcutting that damages fruit branches. To solve this problem, a mechanical-electronic topping prototype was developed that could be adjusted according to the height of cotton. The prototype includes a shearing machine system that can be tuned vertically and an automatic height control system that can detect cotton heights and actuate the mechanical system. This cotton topper was attached to a tractor by a three-point hitch and tested in the field. In the trial, the prototype was tested at ground speeds of 1.1 km/h, 1.5 km/h and 2.2 km/h and excision lengths (from the peak to the cutting point) of 9 cm and 11 cm. Under all tested conditions, the pass rate (the percentage of buds accurately cut without hurting the fruit branch), which reached 74%, was significantly higher than the ideal pass rates of traditional toppers, which were much lower than 50% or even 40%. The dominate factors affecting topping quality were tested. The pass rate was significantly influenced by the forward speed; the missing rate (rate of missed topping) was significantly influenced by the forward speed and excision length; and the overcut rate was significantly influenced by the excision length. The optimized topping speed and excision length were 1.1 km/h and 11 cm respectively, and the other parameters varied according to different user preferences. A replicate trial was conducted and showed that topping at 1.1 km/h and 9 cm prevented further spindling of 90% of the plants, and topping at 1.5 km/h and 11 cm prevented further spindling of 83% of the plants. Keywords: cotton topper, height-adjusting, topping quality, field test, automatic control DOI: 10.3965/j.ijabe.20171002.2492 Citation: Chen Z Y, Shi L. Development and test of an automatic height-adjusting cotton topper. Int J Agric & Biol Eng, 2017; 10(2): 44–55.